Kebijakan Restorative Justice terhadap Tindak Pidana Pencemaran Nama Baik di Media Sosial - Verticallya Yuri S.E Pratiwi; Dey Ravena (UNISBA Press, 2022)
Abstract. Defamation on social media is a crime that damages one's honor through social media. According to Indonesian law, it is a crime that is currently classified as a cyber crime. The rate of reports to the police from cyber crimes continues to increase every year and the number of cases that dominate is defamation on social media. The changing times that occur are accompanied by the presence of a new paradigm as a form of development of criminal law punishment with the presence of restorative justice. Punishment through restorative justice focuses on sentencing with a process of dialogue and mediation. Especially the compensation for the losses caused by the perpetrators to the parties who were harmed, especially the victims. This study aims to determine the effect of restorative justice on the level of criminal defamation on social media that goes to court and to find out restorative justice related to defamation on social media in terms of the Chief of Police Circular SE/2/II/2021. Using a normative juridical research method with an approach to legislation and a concept approach. Through descriptive analytical research specifications, as well as data collection techniques with the method of documentation or document study. The research was analyzed through data analysis with a qualitative approach to primary data and secondary data. Keywords: Defamation, Social Media, Restorative Justice, Circular Abstrak. Pencemaran nama baik di media sosial merupakan kejahatan yang merusak kehormatan seseorang melalui media sosial. Sesuai hukum positif Indonesia, itu merupakan sebuah tindak pidana yang dewasa ini diklasifikasikan sebagai tindak pidana siber. Tingkat laporan ke kepolisian dari tindak pidana siber terus meningkat setiap tahunnya dan jumlah kasus yang paling mendominasi yaitu pencemaran nama baik di media sosial. Perubahan zaman yang terjadi diiringi hadirnya paradigma baru sebagai bentuk perkembangan penghukuman hukum pidana dengan adanya restorative justice. Penghukuman melalui restorative justice berfokus pada pemidanaan dengan proses dialog dan mediasi. Terutama penggantian kerugian yang ditimbulkan oleh pelaku kepada para pihak yang dirugikan, terutama korban. Penelitian ini bertujuan untuk mengetahui pengaruh restorative justice terhadap tingkat tindak pidana pencemaran nama baik di media sosial yang masuk ke pengadilan dan mengetahui restorative justice terkait pencemaran nama baik di media sosial ditinjau dari Surat Edaran Kapolri No. SE/2/II/2021. Menggunakan metode penelitian yuridis normatif dengan pendekatan pada peraturan perundang-undangan dan pendekatan konsep. Melalui spesifikasi penelitian deskriptif analitis, serta teknik pengumpulan data dengan metode dokumentasi atau studi dokumen. Penelitian tersebut dianalisis melalui analisis data dengan pendekatan kualitatif terhadap data primer dan data sekunder. Kata kunci: Pencemaran Nama Baik, Media Sosial, Restorative Justice, Surat Edaran